Keterlibatan Rakyat Kecil dalam Gerakan Reformasi 1998 di Surabaya - Fajar Santoso (Perkumpulan Program Studi Sejarah Se-Indonesia, 2024)
The historical narrative about the 1998 economic crisis has so far only revolved around the student movement and its economic, social and political conditions. How ordinary people fight for reform has not been widely discussed. This article aims to look at the struggles of the small people in Surabaya in the 1998 reform movement. By using historical methods through archival sources, newspapers, books and journals, this article tries to create a historical narrative from the lower classes. The research results show that the role of ordinary people in the 1998 reforms in Surabaya was inseparable from the student movement which was intensively carried out at that time. Small people often join by directly participating in movements carried out by students. On May 5 1998, among the 1,000 students from Unitomo, Untag and Perbanas, there was a cracker seller who took part in a speech demanding reform. On the same day, taxi drivers also demonstrated due to the increase in fuel prices which had a deep impact on the taxi community. On May 9 1998, among thousands of joint students in Surabaya, there was a pedicab driver named Tugiman who led a speech. On May 10 1998, pedicab drivers who were members of Persabaya (Persatuan Becak Surabaya) took part in a mass action at the Airlangga University Library. He shouted for the government to reduce the prices of basic necessities which were soaring at that time. The small people's actions were not only speeches, many small people also provided food assistance to the students who were taking action. One of them was when students stayed overnight at the DPRD Building on 25-27 May 1998.